PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR PADA MATA PELAJARAN GAMBAR BENTUK DI SMK 8 PADANG - Chevi Ajrina Thasya; Mediagus Mediagus (Universitas Negeri Padang, 2020)
This research is a quantitative study that aiims to determine the effect of the STAD type cooperativelearning model on student learning outcomes in subject shape subjects at SMK 8 Padang. With steps 1) improving student learning outcomes, 2) motivating students, 3) forming groups of 4-5 group members, 4) giving assignments in groups, 5) giving quizzes individually, 6) giving evaluations. The research is an experimental research that will examine two classes, namely the experimental class and the control class, the control class selected using purposive sampling technique. Where this research uses pretest and posttest. Then after the research is completed the data is processed using the SPSS program. Fromthe results of the study obtained an average value of experimental class pre-test of 69.50 and the average post-test value of the experimental class was 81.96. The results show that the t-test carried out in the experimental class and the control class produced a t-test of 2.633 and a sig (2-tailed) value of 0.011, while a t-table of 1.669. From the sig value there is a value smaller than the sig-alpha value (0.011 < 0.05) and the tcount is greater than the table (2.633 > 1.669), so the result H0 is rejected. From the description ofthe data it can be concl,uded with the influence of the STAD type cooperative learning model that can influence student learning outcomes in the subject of shape drawing in SMK 8 Padang.Kata Kunci: Penelitian Kuantitatif, Model Pembelajaran, Kooperatif, Hasil Belajar